(untitled) (Experimental biology, 2025)
The demand of fish-derived proteins is growing globally and this poses a huge challenge to the aquaculture sector. As Earlier research has focused mostly on the nutrient requirements and metabolic processes of cultured species, recent findings has also acknowledged that there is a need to understand how the compositions of diets influence physiological responses in farmed fish. This study assessed the proximate nutrient composition of wild and cultured male and female Nile tilapia (Oreochromis niloticus, Linnaeus, 1758). Forty Nile tilapia were sampled with twenty from both sources and equal distribution of sexes. Condition factor assessment showed that both sexes for cultured fish are in better condition compared to their wild counterparts. Proximate analyses comprised moisture, lipid, ash, crude protein, dry matter, crude fiber, and nitrogen-free extract. The means of the data were presented using means and standard error and t-tests were used to determine the differences between the groups. In most of the parameters, there were no statistically significant differences; there was no difference in dry matter, ash, or crude fiber values in the sexes and in origins. However, minimal variations were observed: male tilapia had more crude protein and lipids, and females contained more nitrogen-free extract. This finding offers useful information about the nutrient profile and condition status of O. niloticus and provide information that can support sustainable aquaculture practices, fish processing decisions, and feed formulation.